Three Key Ways That Mentorship Can Support Early Career Scholars - Donald, William E. (GILE Journal of Skills Development, 2023)
Navigating the intrinsic landscape of academia can often feel like attempting to manoeuvre through a maze, especially for individuals at the dawn of their scholarly journey. Drawing on my previous experience as an early career scholar, my current role as a global mentor to emerging scholars, and my decade of research on sustainable careers, I shed light on the profound impact of mentorship for early career scholars. This article uncovers three compelling facets illuminating how mentorship can offer robust scaffolding for these intellectuals. Firstly, we unravel the secret to deciphering the unspoken codes of the academic world, ensuring you are not just a player but a master of the game. Secondly, we explore how taking the reins of your academic destiny can be made more attainable with a mentor's steady support and wisdom. Lastly, we delve into the often overlooked link between mentorship and holistic well-being, emphasising the vital role in nurturing careers and personal fulfilment. Through these insights, we see how mentorship catalyses early career scholars towards heightened productivity, career satisfaction, and an increased likelihood of success in their scholarly pursuits.